Suppression of chatter in high speed milling using microcontroller based speed controller by spindle speed variation method - Yusoff, A. R.; Gebremariam, Mebrahitom Asmelash; Saptaji, Kushendarsyah; Che Ghani, S. A.; Osman Zahid, Muhammed Nafis (2019)
High speed milling process is the most common and versatile technology compared with conventional milling process for machining productivity of metal cutting industry. However, the productivity of machining is often limited by chatter at high signed in milling process. Chatter is a wavy mark on a product surface finish that occurs when self-excited vibration develops during the process, which results in poor surface finish, increase the rate of tool wear and reduce the spindle lifetime. The aims of this study are to suppress chatter by spindle speed variation method at high speed machinery and a better surface finish is also achieved. This research PID controller was developed to give on-line feedback to the machine based on data fed by the microphone sensor. The data received from microphone sensor is analysed in time and frequency domain. Furthermore, after machining, result also was compared with the surface roughness of all cutting conditions. Results showed improvement the surface roughness of the machined material after spindle speed variation has been implemented together with high speed milling technique.